Surgical treatment of pyogenic vertebral osteomyelitis with spinal instrumentation - Chen, Wei-Hua (Springer-Verlag, 2006)
Pyogenic vertebral osteomyelitis responds well to conservative treatment at early stage, but more complicated and advanced conditions, including mechanical spinal instability, epidural abscess formation, neurologic deficits, and refractoriness to antibiotic therapy, usually require surgical intervention. The subject of using metallic implants in the setting of infection remains controversial, although more and more surgeons acknowledge that instrumentation can help the body to combat the infection rather than to interfere with it. The combination of radical debridement and instrumentation has lots of merits such as, restoration and maintenance of the sagittal alignment of the spine, stabilization of the spinal column and reduction of bed rest period. This issue must be viewed in the context of the overall and detailed health conditions of the subjecting patient. We think the culprit for the recurrence of infection is not the implants itself, but is the compromised general health condition of the patients. In this review, we focus on surgical treatment of pyogenic vertebral osteomyelitis with special attention to the role of spinal instrumentation in the presence of pyogenic infection.